A brief study of Rainfall and flood producing Rain Storms in the Beas Catchment (upto Pong) - DHAR, O. N.; NARAYANAN, J. (MAUSAM, 1965)
Mean monthly and annual rainfall for the Beas Catchment based on 1950 rainfall normal have been worked out by isohyetal method. Frequencies of heavy falls of rain of 3 inches and above at eight selected raingauge stations inside the catchment whose data are available for the last 60 years have been worked out. The highest 24-hour rainfall amounts recorded during the four months (July to October) at 17 raingauge stations within the catchment have also been presented after examining their available daily rainfall data. Peak discharge data at Pong dam site for years from 1935 to 1960 were also examined and rain spells corresponding to major floods have been analysed by depth-duration method. On the basis of this analysis design storm rainfall depths have been worked out which have also been maximised for moisture charge.